Single-cell transcriptomics uncovers key immune drivers of vaccine efficacy in cattle - Annaleise Wilson; Pâmela A. Alexandre; Aaron M. Brice; Brad C. Hine; Aaron Ingham; Thibault P. R. A. Legrand; Caroline Royle; Dominic Niemeyer; Antonio Reverter; Stuart E. Denman; Ryan J. Farr (BMC Genomics)
Summary Comprehensive characterization of bovine immune cell populations is essential for improving animal welfare and disease resilience. We performed single-cell RNA sequencing on over 29,000 peripheral blood mononuclear cells (PBMCs) from Angus cattle stratified by delayed-type hypersensitivity (DTH), a proxy for the cellular immune response (Cell-IR). Unsupervised clustering identified major immune populations including CD4⁺ and CD8⁺ T cells, γδ T cells, B cells, monocytes, and dendritic cells. Differential gene expression suggests that low Cell-IR cattle have in elevated NKT inflammatory response, while high Cell-IR cattle have increased CD8- γδ T cell and pro-inflammatory myeloid activity. Intercellular communication analysis using CellChat highlighted pro-inflammatory cytokine cascades, particularly the IL-1β– IL-1R1 ligand-receptor interactions. This study provides a high-resolution atlas of Angus PBMCs and establishes a framework for linking immune cell composition with functional immune phenotypes in cattle.